AAV-mediated transfer of RhoA shRNA and CNTF promotes retinal ganglion cell survival and axon regeneration. (20th February 2017) - Cen, Ling-Ping; Liang, Jia-Jian; Chen, Jian-huan; Harvey, Alan R.; Ng, Tsz Kin; Zhang, Mingzhi; Pang, Chi Pui; Cui, Qi; Fan, You-Ming
Highlights: AAV-RhoA shRNA decreased RhoA expression and promoted neurite outgrowth in vitro . AAV-CNTF promoted RGC survival and axonal regeneration in vivo. AAV-RhoA shRNA alone has weak effects on axonal regeneration in vivo . AAV-RhoA shRNA improved therapeutic effect of AAV-CNTF by two fold in combination. Abstract: The aim of the present study was to determine whether adeno-associated viral vector (AAV) mediated transfer of ciliary neurotrophic factor (CNTF) and RhoA shRNA has additive effects on promoting the survival and axon regeneration of retinal ganglion cells (RGCs) after optic nerve crush (ONC). Silencing effects of AAV-RhoA shRNA were confirmed by examining neurite outgrowth in PC12 cells, and by quantifying RhoA expression levels with western blotting. Young adult Fischer rats received an intravitreal injection of (i) saline, (ii) AAV green fluorescent protein (GFP), (iii) AAV-CNTF, (iv) AAV-RhoA shRNA, or (v) a combination of both AAV-CNTF and AAV-RhoA shRNA. Two weeks later, the ON was completely crushed. Three weeks after ONC, RGC survival was estimated by counting βIII-tubulin-positive neurons in retinal whole mounts. Axon regeneration was evaluated by counting GAP-43-positive axons in the crushed ON. It was found that AAV-RhoA shRNA decreased RhoA expression levels and promoted neurite outgrowth in vitro . In the ONC model, AAV-RhoA shRNA by itself had only weak beneficial effects on RGC axon regeneration. However, when combined with AAV-CNTF, AAV-RhoA shRNA significantly improved the therapeutic effect of AAV-CNTF on axon regeneration by nearly two fold, even though there was no significant change in RGC viability. In sum, this combination of vectors increases the regenerative response and can lead to more successful therapeutic outcomes following neurotrauma.